2017
DOI: 10.1007/s10658-017-1310-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of long-term grapevine response to ‘Candidatus Phytoplasma solani’ infection in the field

Abstract: Bois noir (BN) is the most widespread European grapevine yellows disease caused by 'Candidatus Phytoplasma solani'. Although our knowledge of the mechanisms of interactions of this pathogenic bacteria with host is largely unknown, the plant-pathogen system of BN is commonly used as a model system for studying grapevine yellows diseases. We applied here a conceptual model of general plant pathology -a disease triangle for describing interactions among the host plant, the pathogen and the environment. We generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…For the persistence of symptoms, it is worth noting that only a few of the grapevines persistently showed symptoms, in agreement with Rott et al 47 ; hence, the sanitary status of vineyards infected by BN can be interpreted as a dynamic situation. After the two BN epidemic years (2010, 2011), in 2012 there was initially an increment in symptom remission that was related to the temporary recovered grapevines (tRec; with 1-2 years of recovery).…”
Section: Discussionsupporting
confidence: 87%
“…For the persistence of symptoms, it is worth noting that only a few of the grapevines persistently showed symptoms, in agreement with Rott et al 47 ; hence, the sanitary status of vineyards infected by BN can be interpreted as a dynamic situation. After the two BN epidemic years (2010, 2011), in 2012 there was initially an increment in symptom remission that was related to the temporary recovered grapevines (tRec; with 1-2 years of recovery).…”
Section: Discussionsupporting
confidence: 87%
“…The downregulation of AGO2 here reported in FD condition ( Figure 4 ) could suggest that phytoplasma-infected plants may be more susceptible to virus infection compared to healthy ones. This hypothesis was not confirmed in BNp infected plants, where the presence of phytoplasma did not influence the virus infection ( Rotter et al, 2018 ). However, considering the above-reported differences in molecular and metabolic responses between plants infected by BNp and FDp, we cannot exclude that FDp-infected plants are more sensitive to virus attack, thus opening the venue for future research studies specifically addressed to explore this response.…”
Section: Resultsmentioning
confidence: 98%
“…Salicylic acid studies have revealed that several salicylate biosynthetic genes are up-regulated in the midribs or whole leaves of grapevine infected with the phytoplasma ‘ Ca . P. solani’, e.g., VvICS , which encodes isochorismate synthase, and VvSamt , which encodes S-adenosyl-L-methionine: salicylic acid carboxyl methyltransferase, which catalyzes the formation of the volatile ester methyl salicylate from SA (Hren et al, 2009; Dermastia et al, 2015; Paolacci et al, 2017; Rotter et al, 2018). In addition, quantification of SA and its conjugates in the main leaf veins during infections of grapevine with ‘ Ca .…”
Section: Salicylic Acidmentioning
confidence: 99%